Smart IoT Based Fish Pond Monitoring System to Enhance Fish Cultivation - Priyanka G, Prakash N, Kishore A, Nithesh Kumar S (International Journal of Advanced Science and Technology, 2020)
The objective of this work is to form a smart fish pond monitoring system that assists the owners of fish pond and aquatic planters to produce good quality fish. This system monitors whether normal water levels persist within the fish pond. There is also an automated water flow regulator incorporated to check water level is too high or too low in the fish pond. Water quality has a very high chance of affecting the health of aquatic animals. By using this technique we will measure the important characteristics of the pond water like pH value, cleanness of the water, Air quality and temperature of the pond. With the assistance of Auto feeder and auto water level maintainer the monitoring process becomes very easy. This technique also provides the e-mail notification when anything goes wrong. Remote monitoring of the fish pond becomes very easy by connecting this technique online. Pond cleanness monitoring is an another problem in pond maintenance, we can overcome this problem with the help of Turbidity Sensor and auto water level maintain system and auto feeding system helps to reduce the continuous monitoring. Basically ph meter is used to measures the chemical component as it helps to reduce the Death rate of the fish. Finally the KNN and Decision tree algorithms are trained with the sensor data and tested with another set of data. Prediction is made whether the fish pond is suitable for cultivating fish or not. The KNN algorithm is found to achieve an accuracy of 90% and decision tree achieves an accuracy of 75%.